ANALISI POTENSI PERTANIAN DAN PERKEBUNAN YANG BERDAMPAK PADA EKONOMI DESA MAUTA - Serlin Meri Letding; Sintike Melany Mauyaru; Yusup Laukamang; Petrus Mau Tellu Dony (JOURNAL OF COMMUNITY DEDICATION, 2026)
This research aims to identify the potential of the agricultural sector and its impact on the economic conditions of the community in Mauta Village, Central Pantar District, Alor Regency. Mauta Village possesses abundant natural resources, particularly in commodities such as corn, rice, cashew nuts, and coconuts. The method used in this study is a qualitative approach involving field observations and direct interviews with village officials and local residents. The results indicate that the agricultural sector is the primary livelihood supporting the village economy, where each household manages an average of 2 hectares of land with a total production reaching 49 tons per year. In addition to agriculture, livestock potential in pigs and goats, as well as handicrafts, serve as supplementary income sources. However, village economic development is still hindered by low education levels, limited access to capital, damaged road infrastructure, and the natural disaster threat of Mount Sirung eruptions. This study concludes that optimizing agricultural potential based on local wisdom, supported by infrastructure improvements and MSME assistance, is essential to enhance the welfare of the Mauta Village community sustainably.